Defining remission in childhood-onset lupus: PReS-endorsed consensus definitions by an international task force - Smith, E. M.D.; Aggarwal, A.; Ainsworth, J.; Al-Abadi, E.; Avcin, T.; Bortey, L.; Burnham, J.; Ciurtin, C.; Hedrich, C. M.; Kamphuis, S.; Lambert, L.; Levy, D. M.; et al. (Elsevier, 2024)
Objective: To derive childhood-onset SLE (cSLE) specific remission definitions for future treat-to-target (T2T) trials, observational studies, and clinical practice. Methods: The cSLE International T2T Task Force conducted Delphi surveys exploring paediatric perspectives on adult-onset SLE remission targets. A modified nominal group technique was used to discuss, refine, and agree on the cSLE remission target criteria. Results: The Task Force proposed two definitions of remission: ‘cSLE clinical remission on steroids (cCR)’ and ‘cSLE clinical remission off steroids (cCR-0)’. The common criteria are: (1) Clinical-SLEDAI-2 K = 0; (2) PGA score < 0.5 (0–3 scale); (4) stable antimalarials, immunosuppressive, and biologic therapy (changes due to side-effects, adherence, weight, or when building up to target dose allowed). Criterion (3) in cCR is the prednisolone dose ≤0.1 mg/kg/day (maximum 5 mg/day), whereas in cCR-0 it is zero. Conclusions: cSLE definitions of remission have been proposed, maintaining sufficient alignment with the adult-SLE definition to facilitate life-course research.
Keywords: Childhood-onset SLE; cSLE; Remission; T2T; Treat-to-target